Acacetin Prevents Bone Loss by Disrupting Osteoclast Formation and Promoting Type H Vessel Formation in Ovariectomy-Induced Osteoporosis - Lin, Xiao; Xu, Fang; Zhang, Ke-Wen; Qiu, Wu-Xia; Zhang, Hui; Hao, Qiang; Li, Meng; Deng, Xiao-Ni; Tian, Ye; Chen, Zhi-Hao; Qian, Ai-Rong (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis, characterized by the destruction of bone resorption and bone formation, is a serious disease that endangers human health. Osteoporosis prevention and treatment has become one of the important research contents in the field of medicine. Acacetin, a natural flavonoid compound, could promote osteoblast differentiation and inhibit osteoclast formation in vitro. However, the mechanisms of acacetin on osteoclast differentiation and type H vessel formation, as well as the effect of preventing bone loss, remain unclear. Here, we firstly used primary bone marrow derived macrophages (BMMs), endothelial progenitor cells (EPCs), and ovariectomized (OVX) mice to explore the function of acacetin on bone remodeling and H type vessel formation. In this study, we found that acacetin inhibits osteoclast formation and bone resorption of BMMs induced by the macrophage colony stimulating factor (M-CSF) and receptor activator of nuclear factor-κB ligand (RANKL) in a concentration of 20 μM without exerting cytotoxic eﬀects. It was accompanied by downregulation of osteoclast differentiation marker genes (Ctsk, Acp5, and Mmp9) and cell fusion genes (CD9, CD47, Atp6v0d2, Dc-stamp, and Oc-stamp). Moreover, acacetin disrupted actin ring formation and extracellular acidification in osteoclasts. Mechanistic analysis revealed that acacetin not only inhibits the expression of the major transcription factor NFATc1 and NF-κB during RANKL-induced osteoclast formation, but also suppresses RANKL-induced the phosphorylation of Akt, GSK3β, IκBα, and p65. Additionally, acacetin enhanced the ability of M-CSF and RANKL-stimulated BMMs to promote angiogenesis and migration of EPCs. We further established that, in vivo, acacetin increased trabecular bone mass, decreased the number of osteoclasts, and showed more type H vessels in OVX mice. These data demonstrate that acacetin prevents OVX-induced bone loss in mice through inhibition of osteoclast function and promotion of type H vessel formation via Akt/GSK3β and NF-κB signalling pathway, suggesting that acacetin may be a novel therapeutic agent for the treatment of osteoporosis.